Innovative technologies for the formation and assessment of competencies and skills in the XXI century - Efremova, Nadezhda; Shapovalova, Olga; Huseynova, Anastasia (E3S web of conferences, 2020)
The paper classifies and generalizes innovative technologies for assessing the competencies and skills of the 21st century students in the education system. Taking into account the requirements of the international academic community, criteria for assessing students' competencies in the context of the formation of functional literacy, the ability to study and evaluate independence, global competence and meta-subject skills (soft skills) are considered. The necessity of ensuring continuity of assessment of students' competencies at the levels of general and higher education, as well as the results of formative assessment as an integrative innovative educational technology for the formation, control and evaluation of educational achievements, is emphasized. The possibilities of formative assessment for the development of meta-subject competencies of students are considered. It contains information on the innovative Evidence-Centered Design competency assessment methodology, which contributes to the further development of control and evaluation activities to ensure reliable and valid assessment of students’ achievements and quality assurance in a competency-based approach.